2017
DOI: 10.1016/j.freeradbiomed.2017.10.373
|View full text |Cite
|
Sign up to set email alerts
|

Increased serotransferrin and ceruloplasmin turnover in diet-controlled patients with type 2 diabetes

Abstract: Type 2 diabetes mellitus (T2DM) is associated with oxidative stress and perturbed iron metabolism. Serotransferrin (Trf) and ceruloplasmin (Cp) are two key proteins involved in iron metabolism and anti-oxidant defense. Non-enzymatic glycation and oxidative modification of plasma proteins are known to occur under hyperglycemia and oxidative stress. In this study, shotgun proteomics and 2H2O-based metabolic labeling were used to characterize post-translational modifications and assess the kinetics of Trf and Cp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 55 publications
2
41
0
1
Order By: Relevance
“…These changes were associated with lower levels of adiponectin, an adipose-tissue-derived peptide that was negatively related to CETP activity. The study extends upon our prior research [28,33] and demonstrates that mild hyperglycemia alters HDL dynamics in the early stages of diabetes.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These changes were associated with lower levels of adiponectin, an adipose-tissue-derived peptide that was negatively related to CETP activity. The study extends upon our prior research [28,33] and demonstrates that mild hyperglycemia alters HDL dynamics in the early stages of diabetes.…”
Section: Discussionsupporting
confidence: 78%
“…Non-enzymatic modification (glycation) has been shown to reduce protein stability [53,61] via protein cross-linking and changes in peptide charge, HDL protein conformation, is altered [62]. Recently, we demonstrated that increased degradations of two HDL proteins, ApoA-I and transferrin in normolipidemic diet-controlled subjects with T2D are related to their post-translational glycation [28,33]. Additionally, small lipid-poor HDL particles may be prone to cleavage and degradation as a result of glycation [61,63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The gel was stained with Coomassie blue and the five most abundant bands including one at the molecular weight of 130 kD (expected to be for TRAPPC9, MW 128 233.2 Da) Total protein (100 µg) was combined with 10 µg of TRAPPC9 antibody with protein A/G magnetic beads.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Although Cp does not form a stable complex with transferrin (Tf) [8], its physiological function is acceleration of loading into Tf of ferric ions produced during Cp-catalyzed ferroxidase reaction [9]. Recently the glycation sites in both Cp and Tf were identified in T2D patients [10,11]. However, no significant correlations between HbA1c and serum iron, as well as between HbA1c and TIBC were found in T2D [12].…”
Section: Introductionmentioning
confidence: 99%